Effects of injection parameters, boost, and swirl ratio on gasoline compression ignition operation at idle and low-load conditions. (October 2017) - Kodavasal, Janardhan; Kolodziej, Christopher P; Ciatti, Stephen A; Som, Sibendu
In this work, we study the effects of injector nozzle inclusion angle, injection pressure, boost, and swirl ratio on gasoline compression ignition combustion. Closed-cycle computational fluid dynamics simulations using a 1/7th sector mesh representing a single cylinder of a four-cylinder 1.9 L diesel engine, operated in gasoline compression ignition mode with 87 anti-knock index (AKI) gasoline, were performed. Two different operating conditions were studied—the first is representative of idle operation (4 mg fuel/cylinder/cycle, 850 r/min), and the second is representative of a low-load condition (10 mg fuel/cylinder/cycle, 1500 r/min). The mixture preparation and reaction space from the simulations were analyzed to gain insights into the effects of injection pressure, nozzle inclusion angle, boost, and swirl ratio on achieving stable low-load to idle gasoline compression ignition operation. It was found that narrower nozzle inclusion angles allow for more reactivity or propensity to ignition (determined qualitatively by computing constant volume ignition delays) and are suitable over a wider range of injection timings. Under idle conditions, it was found that lower injection pressures helped to reduce overmixing of the fuel, resulting in greater reactivity and ignitability (ease with which ignition can be achieved) of the gasoline. However, under the low-load condition, lower injection pressures did not increase ignitability, and it is hypothesized that this is because of reduced chemical residence time resulting from longer injection durations. Reduced swirl was found to maintain higher in-cylinder temperatures through compression, resulting in better ignitability. It was found that boosting the charge also helped to increase reactivity and advanced ignition timing.